2022
DOI: 10.3390/ijms23169118
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Mitochondrial SIRT3 Ameliorates Ischemia-like Injury in Human Endothelial Cells

Abstract: Structural and functional alterations of vasculature caused by age-related factors is critically involved in the pathogenesis of ischemic stroke. The longevity genes sirtuins (SIRTs) are extensively investigated in aging-associated pathologies, but their distinct roles in ischemic stroke still remain to be clarified. To address this question, we applied oxygen and glucose deprived/reperfusion (OGD/R) to induce ischemic injury in human endothelial cells (ECs), which are the main component of vasculature in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lentivirus was prepared as previously reported [29]. In brief, we transfected HEK293T cells with psPAX2 (15 µg), pMD2.G (10 µg), and FUGW-SIRT1 (20 µg) plasmids using polyethyleneimine (PEI).…”
Section: Lentivirus Preparation and Infectionmentioning
confidence: 99%
“…Lentivirus was prepared as previously reported [29]. In brief, we transfected HEK293T cells with psPAX2 (15 µg), pMD2.G (10 µg), and FUGW-SIRT1 (20 µg) plasmids using polyethyleneimine (PEI).…”
Section: Lentivirus Preparation and Infectionmentioning
confidence: 99%
“…Recent studies have found that modulating the tunneling nanotubes formation and transcellular mitochondria transfer is a promising strategy for the treatment of ischemic stroke ( Luchetti et al, 2022 ), however, the relationship between Sirt3 and tunneling nanotubes formation and transcellular mitochondria transfer remains unclear. Changes in the blood-brain barrier directly caused by endothelial injury play a significant role in the pathogenesis of ischaemic stroke ( Yang X. et al, 2021 ), and SIRT3 plays a critical role in alleviating vascular endothelial injury after stroke ( Liu et al, 2022 ). In addition, SIRT3 can aid neurovascular recovery in an ischaemic stroke model ( Yang X. et al, 2018 ).…”
Section: The Role Of Sirt3 In I/r Brain Injurymentioning
confidence: 99%
“…This mechanism could be associated with the deacetylating of FOXO3a, increasing the activity of the antioxidant enzyme SOD2 and reducing ROS production [ 17 ]. Similarly, recent evidence indicates that SIRT3 overexpression effectively attenuates ROS overproduction induced by oxygen–glucose deprivation/reperfusion (OGD/R) in HUVECs [ 107 ].…”
Section: Sirtuins In Ischemic Strokementioning
confidence: 99%